Spelling Tartessian (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2021)
This paper examines the consonant groups attested in Tartessian or the language of the South-western inscriptions. A comparison with Celtiberian spelling strategies leads to the question how Tartessian could write groups beginning with a stop, if they existed.
Keywords: Tartessian consonant groups; Spelling strategies; Potentially mute vowels